A questão educacional nas obras de Karl Marx e Friedrich Engels - Netto, Mario Borges (2013)
This dissertation intends to problematize the propositions of Marx and Engels about education, it has the critics to the capitalist way of production and the necessity of its overcoming as its reference. In order to do that, it is organized in two parts: in the first one we investigate the historical context in which Marx and Engels lived, with the purpose of better understanding the material basis of the historical dialectical materialism. In the second part, we problematize the European instruction in XVIII and XIX centuries and the inclusion of Marx and Engels in the educational debate of their time. Through the research it is possible to perceive that the educational issue in the work of Marx and Engels is associated to the studies about the development of the capitalist way of production and its contradictions in the organization of social life. That means, therefore, it is necessary to consider the function that school education has to the maintenance and spread of capitalism, as well as, conversely, it contributes to the revolutionary project of the working class aiming the construction of communism. When we concluded this dissertation we noticed that Marx and Engels didn t construct pedagogy, or even an educational theory, but a vast theoretical system about a capitalist society that, in its totality, has embraced the questions about human formation, education of the working class and of public instruction. However, we understand the Marxian legacy as a revolutionary perspective that remains modern in the revealing of the capitalist society, because it makes it enable and potentialize the revolutionary transformation of reality. Consequently, the studies of Marx and Engels are necessary to the problematization of education, which proposes the overcoming of the dichotomy between manual work and intellectual work, between thinking and doing, and by doing that it makes the intransigent defense of a complete human formation, centered in contents that are beyond the order of capitalism.